Spectroscopic monitoring of mechanical forces during protein folding by using molecular force probes - Neudecker, Tim; Hoffmann, Marvin; Dreuw, Andreas (ChemPhysChem, 2016)
Detailed folding pathways of proteins are still largely unknown. Real-time monitoring of mechanical forces acting in proteins during structural transitions would provide deep insights into these highly complex processes. Here, we propose two molecular force probes that can be incorporated into the protein backbone to gain insight into the magnitude and direction of mechanical forces acting in proteins during natural folding and unfolding through their optical spectroscopic response. In fact, changes in the infrared and Raman spectra are proportional to the mechanical force deforming the force probes, and the relevant bands can be intensified and shifted to a transparent window in the protein spectrum by isotopic substitution. As a result, the proposed molecular force probes can act as “force rulers”, allowing the spectroscopic observation and measurement of mechanical forces acting within the proteins under natural conditions without external perturbation.